BUDAYA OGANISASI MEMODERASI PENGARUH KEPRIBADIAN DAN STRESS KERJA TERHADAP KINERJA GURU PADA SMP PL SEMARANG, SALATIGA DAN AMBARAWA - Wibowo, Yohanes Ari; Basiya, R. (Jurnal Ilmiah Telaah Manajemen, 2015)
The purpose of the study is to examine the influence of working stress and personality toward theteachers' performance in Junior High School Pangudi Luhur Semarang, Salatiga,and Ambarawa with organization of culture as a moderation variable. The population of this study used 118 teachers. Based on the result of the study can be concluded as follow: personality has influence toward teachers' performance, working stress has no influence toward teacher's performance, organization of culture has influence toward teachers' performance, organization of culture moderate the influence of working stress toward teachers' performance, and organization of culture moderate the influence of personality toward teachers' performance. Keywords:work stress, organizational culture, personality and teachers performance